2014
DOI: 10.1007/s00264-014-2510-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of joint failure in hip prostheses infected with Staphylococcus aureus treated with debridement, antibiotics and implant retention compared to Streptococcus

Abstract: DAIR-treated patients with prosthetic hip joint infections due to S. aureus tended to have worse outcomes than those infected with Streptococcus spp. The specific influence of the infecting pathogen should be considered in future guidelines and recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
(37 reference statements)
1
36
1
2
Order By: Relevance
“…Accordingly, the authors suggested that the decision for I&D with retention of the knee prosthesis should be dependent in the first instance on the nature of the infecting pathogen. Betz et al [60] reported similar results in infected hip arthroplasties, with an average 21% failure rate of Staphylococcus aureus infections compared to no failure of streptococcal infections treated with DAIR. Interestingly, Lora-Tamayo et al [31] reported that the treatment of MRSA PJIs was not less successful than methicillin-susceptible Staphylococcus aureus (MSSA) infections if rifampin-based antibiotic combinations were administered during the first 30 days after debridement to both groups.…”
Section: Prognostic Factors For Infection Controlmentioning
confidence: 87%
See 1 more Smart Citation
“…Accordingly, the authors suggested that the decision for I&D with retention of the knee prosthesis should be dependent in the first instance on the nature of the infecting pathogen. Betz et al [60] reported similar results in infected hip arthroplasties, with an average 21% failure rate of Staphylococcus aureus infections compared to no failure of streptococcal infections treated with DAIR. Interestingly, Lora-Tamayo et al [31] reported that the treatment of MRSA PJIs was not less successful than methicillin-susceptible Staphylococcus aureus (MSSA) infections if rifampin-based antibiotic combinations were administered during the first 30 days after debridement to both groups.…”
Section: Prognostic Factors For Infection Controlmentioning
confidence: 87%
“…One of the most recognized factors associated with high failures is infection due to methicillin-resistant Staphylococcus aureus (MRSA) [69]. The poor prognosis and high risk of re-infection due to MRSA is linked to the limited availability of selective antibiotics and the potential insurgence of glycopeptide resistance in vancomycin-treated patients [60, 70]. Zürcher-Pfund et al [71] treated 21 infected TKRs with a combination of debridement and antibiotics and followed them up for a mean of 7 years.…”
Section: Prognostic Factors For Infection Controlmentioning
confidence: 99%
“…Lora-Tamayo et al [24] In earlier studies, the factors associated with poor outcomes in DAIR-treated PJIs included S. aureus infection [8,10,11,26,27], coagulase-negative Staphylococcus infection [9,11], and polymicrobial infection [12]. S. aureus PJIs have been shown to have worse outcomes than PJIs caused by Streptococcus species [27,28]. Infections by methicillinresistant S. aureus (MRSA) have been suggested to have a worse prognosis than infections by methicillin-susceptible S. aureus (MSSA), but this finding is controversial [12].…”
Section: Discussionmentioning
confidence: 97%
“…Debridement, antibiotic and implant retention has excellent results for non-resistant Streptococcal PJI, with 100% success in one series of 14 cases [124]. However, prosthesis retention has been significantly associated with treatment failure of Enterococcal PJIs, particularly if they present greater than 2 years after the index arthroplasty [37].…”
Section: Managementmentioning
confidence: 99%